Ride comfort assessment in off road vehicles using passive and semi-active suspension - Faris, Waleed Fekry; BenLahcene, Zohir; Ihsan, Sany Izan (2009)
Vehicles handling and ride comfort are essential subject because these vehicles operate at different environments. Improving the comfort ability enables the drivers to derive for a long time at critical situations with full activity. This paper deals with dynamics and control policies analysis of semi-active suspension systems for off-road vehicles. Three configurations of these vehicles; 2-axle, 3-xle and 4-axles have been studied and their performances are compared. The application of several control policies of semi-active suspension system, namely skyhook; ground-hook and hybrid controls have been analyzed and compared with passive systems.The results show that the hybrid control policy yields better comfort than a passive suspension, without reducing the road-holding quality or increasing the suspension displacement. The hybrid control policy is also shown to be a better compromise between comfort, road-holding and suspension displacement than the skyhook and ground-hook control policies. Skyhook control generally improves sprung mass responses while at the same time increase unsprung mass responses. On the other hand, ground-hook control generally improves unsprung mass responses at the expense of the sprung mass responses. Ground-hook control also found to take longer time to settle in transient state response. Results show an improvement in ride comfort and vehicle handling using 4-axle over 3-axle and 2-axle when emphasis is placed on the response of the vehicle body acceleration, suspension and tyre deflection.